Explicitly defined empirical constant for phase-change simulation in a two-phase closed thermosyphon - Cho, Sehyeon; Kong, Dayoung; Geum, Gyohoon; Lee, Seungjae; Park, Junrae; Lee, Seong Hyuk; Lee, Jungho; Lee, Hyoungsoon (International Communications in Heat and Mass Transfer, 2024)
Over several decades, the importance of energy recovery has grown because of the global shift from fossil fuels to renewable energy sources. Among various energy-recovery approaches, waste heat recovery has emerged as a prominent method owing to its ease of adoption in various fields such as power plants and commercial buildings and high amount of recovery by adopting in the heavy industry. A heat exchanger with a heat pipe offers superior waste heat recovery efficiency through its highly effective heat transfer in a two-phase closed thermosyphon (TPCT). Numerous investigations have explored the thermal hydraulic performance of TPCTs in various geometries and operation conditions, mostly relying on experimental methods owing to the challenges in accurately simulating phase change in TPCT systems. These challenges arise from using the mass-transfer intensity factor, r—an empirically selected constant in phase-change models—which lacks a robust basis in fundamental principles. This study introduces a novel approach to selecting the r value for simulating the phase-change process in TPCTs. By employing the volume-of-fluid model for multiphase interfaces along with the widely used Lee model for phase change, the proposed model establishes a correlation between evaporation and condensation mass fluxes to define the r value in condensation heat transfer within a TPCT. The utilisation of the proposed model in simulations yielded improved temperature predictions, deviating by 4–7 K from experimental results while offering a significant reduction in the number of r values to choose from, achieved by explicitly defining the r value for condensation heat transfer. The conventional approach was to set both empirical constants to re = rc = 0.1 s−1. However, this model, which provides a relationship between the two empirical constants based on mass balance, revealed that rc should be 9.8 s−1 rather than 0.1 s−1 corresponding to re = 0.1 s−1. Furthermore, the study examines the diverse thermal performance outcomes associated with varying r values for evaporation in a wide range of re (0.1–100 s−1). rc was in the range of 9.8–12.7 s−1, denoting an increase of only 30% as re increased 1000 times from 0.1 to 100 s−1. This research offers a comprehensive understanding of the computational modelling of TPCTs, providing valuable insights into their thermal characteristics based on the intricate phase-change phenomena occurring within them.
Keywords: Empirical constants; Energy recovery; Explicitly defined; Intensity factors; Mass transfer intensity factor; OpenFOAM; Phase Change; Phase change model; R value; Two-phase closed thermosyphon; Explicitly defined; Mass transfer intensity factor; OpenFOAM; Phase-change model; Two-phase closed thermosyphon